2007
DOI: 10.1186/gb-2007-8-10-r230
|View full text |Cite
|
Sign up to set email alerts
|

On the association between chromosomal rearrangements and genic evolution in humans and chimpanzees

Abstract: Background: The role that chromosomal rearrangements might have played in the speciation processes that have separated the lineages of humans and chimpanzees has recently come into the spotlight. To date, however, results are contradictory. Here we revisit this issue by making use of the available human and chimpanzee genome sequence to study the relationship between chromosomal rearrangements and rates of DNA sequence evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 196 publications
2
23
2
Order By: Relevance
“…However, this was not the case. On the contrary, in some of the inverted regions, a lower degree of divergence has been observed (Lu et al 2003, Zhang et al 2004, Vallender & Lahn 2004, Mikkelsen et al 2005, Szamalek et al 2007, Marques-Bonet et al 2007). …”
Section: Large Pericentric Inversionsmentioning
confidence: 85%
“…However, this was not the case. On the contrary, in some of the inverted regions, a lower degree of divergence has been observed (Lu et al 2003, Zhang et al 2004, Vallender & Lahn 2004, Mikkelsen et al 2005, Szamalek et al 2007, Marques-Bonet et al 2007). …”
Section: Large Pericentric Inversionsmentioning
confidence: 85%
“…In recent years, intermediate-scale mutations (e.g., insertion, deletion, translocation, and inversion) that result in structural variation have gained considerable attention (1). Although the genome-wide impact of mutations of different sizes (e.g., single-nucleotide changes and structural alterations such as insertion or deletion of genetic material) has been investigated separately, it has long been speculated (2,3), and increasing evidence suggests, that mutations of different sizes are correlated in prokaryotes and eukaryotes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Although these studies have provided evidence for such a relationship, how this phenomenon affects functional elements in the genome has not been systematically investigated in humans.…”
mentioning
confidence: 99%
“…Indeed the hypothesis that they affected the rate of genetic divergence between humans and chimpanzees does not have enough support (Kehrer-Sawatzki and Cooper 2007). Previous studies revealed no evidence of accelerated evolution for genes on rearranged versus colinear chromosomes (Lu et al 2003;Navarro and Barton 2003;Vallender and Lahn 2004;Zhang et al 2004;The Chimpanzee Sequencing and Analysis Consortium 2005;Marques-Bonet et al 2007) and showed that chromosomal rearrangements have generally no impact on gene expression except in a few particular cases (Munoz and Sankoff 2012). However, chromosomal rearrangements appear to be associated with higher divergence in gene-expression levels in the brain (Marques-Bonet et al 2004) and genes located on rearranged chromosomes showed reduced recombination rate compared with colinear ones (Farre et al 2013).…”
mentioning
confidence: 99%